2022
DOI: 10.3390/bs13010024
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy as a Predictor of Work Performance: The Mediating Role of Lifelong Learning and Creativity

Abstract: This study examined the effect of information literacy (IL) on work performance with mediating role of lifelong learning and creativity among journalists in Pakistan. A cross-sectional survey using an online questionnaire was conducted in the press clubs of four provinces (e.g., Punjab, Sindh, Khyber Pakhtunkhwa, and Baluchistan) and the federal capital Islamabad for data collection. The received 1084 responses were analyzed using the partial least squares structural equation modelling. The results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…IL enables employees to make need-based and informed decisions that ultimately improve their work performance. This result corroborated the findings of Naveed et al . (2023) who reported IL as a predictor of work performance through the mediation of lifelong learning and creativity.…”
Section: Discussionsupporting
confidence: 93%
“…IL enables employees to make need-based and informed decisions that ultimately improve their work performance. This result corroborated the findings of Naveed et al . (2023) who reported IL as a predictor of work performance through the mediation of lifelong learning and creativity.…”
Section: Discussionsupporting
confidence: 93%
“…This finding also corroborated the outcomes of a recent and similar study by [ 16 ] who reported that digital literacy predicts positively creative thinking disposition. Similarly, the study by Naveed et al [ 64 ] also reported the positive impact of information literacy one creativity among Pakistani journalists. Hence, the higher information literacy capabilities increase creative skills in the context of academia.…”
Section: Discussionmentioning
confidence: 66%
“…In a recent study by Kesici [ 16 ], a somehow similar outcome was reported that the digital literacy of Turkish teachers influences positively their lifelong learning disposition. Likewise, Naveed et al [ 64 ] also reported information literacy as a predictor of lifelong learning among journalists in Pakistan. Thus, it may be concluded that information literacy skills improve lifelong learning in the academic context.…”
Section: Discussionmentioning
confidence: 99%
“…e) Carecer de habilidades para pensar creativamente y organizar las ideas antes de escribir un documento científico, es un elemento recurrente en los docentes, esto debido la complejidad de demostrar habilidades y estrategias de cómo utilizar el lenguaje adecuado, concretizar ideas deseadas y lograr producir redacción propia para el público al que se dirige el contenido, todo ello puede inhibir la creación de textos (Hempel, 2013;Naveed, 2023).…”
Section: Visiones De Las Barreras/competencias Lingüísticas Y La Comu...unclassified
“…La propuesta principal para vencer las BL en la comunicación de la ciencia radica en muchos aspectos, entre los más concretos se encuentran: (1) fomentar estrategias de escritura y comunicación científico-académica durante los posgrados con el objeto de producir textos científicos (Garza-Almanza, 2014;Espino Datsari, 2015); y (2) apoyar la enseñanza para involucrar valores, creencias y cultura sobre textos científicos que van más allá de los meros contenidos (Naveed, 2023). Una repercusión probable de tener CL es el desarrollo profesional que emerge con un sistema de influencia en sus decisiones sobre que ideas y recursos son propios para lograr tal desarrollo.…”
Section: Visiones De Las Barreras/competencias Lingüísticas Y La Comu...unclassified